The Effect of Third-Party Funds on Profitability with Market Risk and Inflation as Moderating Variables - Kadek Mitta Pradila Yuardi; I Gst Ayu Eka Damayanthi (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
The profitability of Village Credit Institutions (LPDs) is influenced by their ability to collect and manage Third-Party Funds (TPF) optimally. However, economic dynamics such as market risk and inflation may weaken the effect of TPF on profitability. This study aims to examine the effect of Third-Party Funds on profitability with market risk and inflation as moderating variables. The research was conducted on LPDs operating in Denpasar City during the 2021–2023 period using 92 financial report observations obtained through purposive sampling. Profitability is measured using Return on Assets (ROA), market risk is proxied by the Net Interest Margin (NIM), and inflation is proxied by the Consumer Price Index (CPI). This study employs a quantitative approach using the Moderated Regression Analysis (MRA) technique. The results show that Third-Party Funds have a positive and significant effect on profitability. Market risk significantly weakens the relationship between Third-Party Funds and profitability, while inflation is not proven to be a moderating variable in this relationship.